Insecticidal Action of Local Isolates of Entomopathogenic Fungi Against Bactrocera oleae Pupae - Spiridon Mantzoukas; Alexandros Margaritis; Thomais Sourouni; Vasiliki Georgopoulou; Chrysanthi Zarmakoupi; Vasileios Papantzikos; Ioannis Lagogiannis; Panagiotis A. Eliopoulos; George Patakioutas (Biology, 2024)
In this work, the ability of certain entomopathogenic fungi to control the olive fruit fly Bactrocera oleae (Diptera: Tephritidae), which significantly affects olive cultivation, was assessed. First, entomopathogenic fungi that often contribute to reducing pests, as well as B. oleae, were sought out. Puparia of B. oleae were collected from oil mills, and soil samples were collected from various olive grove regions of Greece. These soils were used as the substrate in which the effect of the entomopathogenic fungi on the B. oleae pupae was studied. In addition, the same treatments were studied in non-soil conditions. The results show that certain known entomopathogenic fungi are able, in their natural environment, to kill B. oleae pupae to a significant extent. The survival time for adults (days) was lower in the presence of Beauveria bassiana (Hypocreales: Cordycipitaceae), at 13.20 in the soil (5.56 ± 0.42) and non-soil (6.76 ± 0.46) conditions, compared to that of the control in soil (9.83 ± 083) and non-soil (9.90 ± 0.72) conditions. This is encouraging for Mediterranean regions where the presence of B. oleae significantly affects olive cultivation, while quality olive oil is in high demand.